Evaluasi dan Perbaikan Antarmuka Aplikasi Mobile IZAT (Aplikasi Zero Accident Assistant) Bidang K3 PT PJB UP Gresik Menggunakan Metode Human-Centered Design - Dienabillah Gita Fitri; Herman Tolle; Hanifah Muslimah Az-zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
IZAT is an application developed by K3 Field PT PJB UP Gresik. In its use, several problems were encountered related to navigation and layout of the apps. With the usability problem, IZAT needs to be evaluated in relation to five aspects of usability by Nielsen. Improvements will be made using the Human-Centered Design method and using usability testing (learnability, efficiency, memorability, and error) and a modified SUS questionnaire (satisfaction) for testing method. Respondents consisted of two types, namely K3 and Non K3 Field respondents. From the test results obtained data increase of 33.35% for each type of respondent in the aspect of learnability, 45.3% for in the K3 Field and 43.2% for Non K3 in the aspect of efficiency, percentage increase by 5.23% for K3 Field and 2.43% for Non K3 Field at an average time, 4.25% decrease in the percentage of the number of tap in K3 Field and 0% decrease in the percentage of the number of tap in Non K3 Field in memorability aspect. The error aspect resulted in a decrease in the error rate of 21.5% for in the K3 Field and a decrease of 22.6% in the Non K3. SUS score as a measurement of satisfaction aspect obtained an increase of 25.03 in the K3 Field and an increase oh 18.37 in the Non K3 field. From both tests, it is known that solution design has better usability.